Study of UV Index and Total Ozone Climatology Over Bhairahawa, Pokhara, and Lumle in Nepal - Karna, Umakant Lal; Bhattarai, Binod K.; Poudyal, Khem N. (Amrit Research Journal, 2024)
Recent studies on solar ultraviolet (UV) radiation have been pivotal in unveiling its detrimental impacts on humans and other living organisms on Earth. The Ultraviolet Index (UVI) is a crucial tool to ascertain the level of solar ultraviolet radiation at any given location, utilizing data from diverse sources. This study aims to examine the UV Index and Total Ozone Climatology over Bhairahawa (27.52°N, 83.43°E, 109m asl), Pokhara (28.22°N, 83.32°E, 850m asl), and Lumle (28.30°N, 83.80°E, 1740m asl), situated in the mid of Nepal, using OMI/Aura satellite data. The average minimum and maximum UV index recorded are 3.11±1.01 and 7.77±2.25 at Bhairahawa, 4.31±1.36 and 12.90±2.28 at Lumle, and 4.03±1.34 and 10.71±3.38 at Pokhara respectively. Additionally, the minimum Total Ozone Column (TOC) value is observed to be 251.4-288.5DU in December, with the maximum value reaching 291-285.3DU in April across all sites. This study concludes that the solar UV index increases with an increase in altitude, among other influential factors. The exploration of UVI and ozone data from the OMI/AURA satellite over specific locations in Nepal aims to enrich the existing pool of knowledge on solar ultraviolet radiation and its varying intensity, thereby contributing to the comprehension of its harmful implications on living entities.